2018
DOI: 10.1159/000485739
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Use in a Patient with Idiopathic Macular Telangiectasia Type 2

Abstract: Crystalline deposits and neurosensory retinal cavitary changes can develop in both tamoxifen retinopathy and nonproliferative idiopathic macular telangiectasia type 2 (MacTel2). MacTel2 is typically differentiated from tamoxifen retinopathy based on the presence of late leakage and mid-phase telangiectatic vessels on fluorescein angiography (FA) and the presence of hyperautofluorescence. Unlike MacTel2, tamoxifen retinopathy is known to be a progressive disease and the cessation of tamoxifen results in resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…What cannot be ignored is that a similar etiology between tamoxifen-induced rentinopathy and MacTel2 of decreased serum estrogen concentration and functional damage of Müller cells caused similar symptoms [ 9 , 10 ]. Both of these can present CME and yellow-white deposits.…”
Section: Discussionmentioning
confidence: 99%
“…What cannot be ignored is that a similar etiology between tamoxifen-induced rentinopathy and MacTel2 of decreased serum estrogen concentration and functional damage of Müller cells caused similar symptoms [ 9 , 10 ]. Both of these can present CME and yellow-white deposits.…”
Section: Discussionmentioning
confidence: 99%
“…FA allows to differentiate retinal changes related to tamoxifen retinopathy, which may be similar on SD-OCT to the ones found in macular telangiectasia type 2 (MacTel2) [9]. Nevertheless, a late leakage of telangiectatic macular capillaries is observed in FA of eyes with MacTel2 [10]. Thus, the diagnosis of bilateral MH related to tamoxifen toxicity was made.…”
Section: Case Reportmentioning
confidence: 99%
“…There is another set of publications with contrasting results on the progression of MacTel in patients with and without history of tamoxifen use. 7,8 Behrens et al 7 supported the theory that concurrent tamoxifen use in a type 2 MacTel patient could accentuate the fovea atrophy while another paper by Wolf-Schnurrbusch et al suggested that simultaneous use of tamoxifen in a type 2 MacTel did not hasten the structural changes on OCT in type 2 MacTel cases. 8…”
Section: Introductionmentioning
confidence: 96%
“…There is another set of publications with contrasting results on the progression of MacTel in patients with and without history of tamoxifen use. 7,8 Behrens et al 7 supported the theory that concurrent tamoxifen use in a type 2 MacTel patient could accentuate the fovea atrophy while another paper by Wolf-Schnurrbusch et al suggested that simultaneous use of tamoxifen in a type 2 MacTel did not hasten the structural changes on OCT in type 2 MacTel cases. 8 In this retrospective study, we intended to compare the clinical and imaging findings of a subset of patients with and without tamoxifen retinopathy and another subset of patients with type 2 MacTel with and without history of tamoxifen use.…”
Section: Introductionmentioning
confidence: 97%